2008
DOI: 10.1038/nature06892
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis selectively requires the p110α isoform of PI3K to control endothelial cell migration

Abstract: Phosphoinositide 3-kinases (PI3Ks) signal downstream of multiple cell-surface receptor types. Class IA PI3K isoforms couple to tyrosine kinases and consist of a p110 catalytic subunit (p110alpha, p110beta or p110delta), constitutively bound to one of five distinct p85 regulatory subunits. PI3Ks have been implicated in angiogenesis, but little is known about potential selectivity among the PI3K isoforms and their mechanism of action in endothelial cells during angiogenesis in vivo. Here we show that only p110al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
441
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(474 citation statements)
references
References 26 publications
26
441
3
Order By: Relevance
“…3c), which differed from the effects of p110α knockdown [10][11][12][13] . However, C2α knockdown markedly inhibited VEGF-A-induced phosphorylation of MYPT1, a substrate of Rho kinase (Fig.…”
Section: C2α Is Involved In Endothelial Migration Proliferation and mentioning
confidence: 94%
See 2 more Smart Citations
“…3c), which differed from the effects of p110α knockdown [10][11][12][13] . However, C2α knockdown markedly inhibited VEGF-A-induced phosphorylation of MYPT1, a substrate of Rho kinase (Fig.…”
Section: C2α Is Involved In Endothelial Migration Proliferation and mentioning
confidence: 94%
“…These C2α actions underlie its roles in angiogenesis and barrier integrity. The actions of C2α and class I PI3Ks in EC are distinct in that, different from C2α, class I PI3Ks exert a great impact on Akt stimulation and cell proliferation and are not involved in vesicular trafficking including VE-cadherin transfer or VE-cadherin assembly at the cell-cell junction [10][11][12][13] . Therefore, these observations reveal novel biological activities of C2α and underscore broader roles for PI3K family members in vascular physiology and pathophysiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have demonstrated that the p110a and p110b isoforms play distinct roles in cellular signaling, growth, and oncogenic transformation. It has been shown in mice, for example, that both p110a and p110b contribute to insulin action in the liver (Foukas et al 2006;Ciraolo et al 2008;Jia et al 2008;Sopasakis et al 2010), whereas angiogenesis and vascular endothelial growth factor (VEGF) signaling require p110a but not p110b (Graupera et al 2008). Interestingly, while p110a is essential for lung adenocarcinoma induced by Kras (Gupta et al 2007), p110b is required for prostate tumorigenesis driven by Pten loss in mice (Jia et al 2008).…”
mentioning
confidence: 99%
“…On the other hand, there are several cancer types that have been reported to have elevated levels and/or genomic amplifications of these other isoforms, indicating that they too may contribute to cancer (13,14). In addition, activation of receptor tyrosine kinases such as VEGF receptor, EGF receptor, PDGF receptor, or human epidermal growth factor receptor 2 (HER2) leading to the activation of the PI3K pathway usually requires p110α for signaling and tumorigenesis (15)(16)(17). Rat sarcoma (Ras) proteins, which signal in part through PI3K pathway, are also frequently mutated in human cancer (18,19).…”
mentioning
confidence: 99%